Public-private partnership in model of advisory-diagnostic center - Kravchenko, V. V. (Journal of Education, Health and Sport, 2017)
Introduction The transition of the Ukrainian health care system to progressive development models that ensure its structural efficiency is an actual problem.Purpose: to design the functional-organizational model of the Consultative and Diagnostic Center (CDC) on the principles of public-private partnership (PPP).Materials and methods General scientific methods of analysis, synthesis, generalization, interpretation of scientific data, as well as systemic and structural-functional approaches were applied.Results The model of the consulting and diagnostic center is developed as a new organizational and legal form of medical services for the population on the principles of PPP.ConclusionsThe developed model is a new organizational and legal form of medical services for the population, implements the transition of communal services to the mechanisms of public-private partnership, provides attraction of private investments to achieve medical, social and economic efficiency of CDC and increasing the availability and quality of medical care.